Diversity and threats to trees and shrubs in the courtyards of the blessed Al-Aqsa Mosque in the city of Al-Quds (Jerusalem), Palestine - ABDEL FATTAH N. ABD RABOU; ABBOUD Y. EL-KICHAOUI; EQBAL S. RADWAN; EMAN J. AL-BALAWI; AYAT A. ABBAS; KAMAL E. ELKAHLOUT; DAOUD I. AL-HALI; MOHAMMED A. ABD RABOU; ASMAA A. ABD RABOU; ROLA I. JADALLAH; KHALID A. HUSSEIN; MOHAMAD ABOU AUDA; ABED AL QADER I. HAMMAD; INAS A. ABD RABOU; OTHMAN A. ABD RABOU; NAWAL F. ABD RABOU; ASHRAF A. SHAFEI; NEDAL A. FAYYAD; AYMAN W. DARDONA; ZUHAIR W. DARDONA; FATMA A. MADKOUR; HASHEM A. MADKOUR; NORMAN A. KHALAF; MOHAMMED R. AL-AGHA (Society for Indonesian Biodiversity, 2024)
Abstract. Abd Rabou AFN, El-Kichaoui AY, Radwan ES, Al-Balawi EJ, Abbas AA, Elkahlout KE, Al-Hali DI, Abd Rabou MA, Abd Rabou AA, Jadallah RI, Hussein KA, Abou Auda M, Hammad AAQI, Abd Rabou IA, Abd Rabou OA, Abd Rabou NF, Shafei AA, Fayyad NA, Dardona AW, Dardona ZW, Madkour FA, Madkour HA, Khalaf NA, Al-Agha MR. 2024. Diversity and threats to trees and shrubs in the courtyards of the blessed Al-Aqsa Mosque in the city of Al-Quds (Jerusalem), Palestine. Biodiversitas 25: 4462-4478. The blessed Al-Aqsa Mosque in the city of Al-Quds (Jerusalem), Palestine, which extends over an area of 144,000 square meters, is of great importance to Palestinians, Arabs, and Muslims. Despite the many studies that have addressed the various features of the blessed Al-Aqsa Mosque, the vegetation cover has been rarely written about. This current descriptive study aims to enumerate the trees and shrubs that adorn the courtyards of the blessed Al-Aqsa Mosque. The study relied on continuous visits, observations, and discussions since 2020. A direct inventory of the trees and shrubs was conducted in terms of species and numbers, and they were classified according to the available guidebooks. Photographs were taken for documentation and verification purposes. The number of trees and shrubs in the courtyards of the blessed Al-Aqsa Mosque amounted to 1,042 trees and shrubs. The recorded trees and shrubs consisted of 30 species belonging to 20 families and 14 orders. Gymnosperms included 4 species (13.3%), while angiosperms included 26 species (86.7%). The European Olive (Olea europea L.) was the most widespread species with 550 individuals (52.78%), followed by the Evergreen Cypress (Cupressus sempervirens L.) with 274 individuals (26.29%), and the Aleppo or Jerusalem Pine (Pinus halepensis Mill.) with 85 individuals (8.16%). The number of recorded tree species amounted to 20 species (66.7%), while the number of shrub species amounted to 10 species (33.3%). Exotic trees or shrubs constituted 21 species (70.0%), while the rest (30.0%) were native. Threats to the trees and shrubs of Al-Aqsa Mosque included Israeli excavations under Al-Aqsa Mosque and its courtyards, Israel's use of some toxic and chemical materials to break up the soil and facilitate excavations, cutting down trees and shrubs for Israeli security purposes, burning trees and shrubs due to Israeli military actions, Israel's prevention of replanting or planting trees and shrubs, severe storms and strong winds, and diseases. If conditions permit, it is recommended to plant woody plant species that are compatible with the prevailing environmental and ecological conditions in Palestine, which add splendor to the courtyards of this great historical Islamic place in Palestine.